Implementasi Pendidikan Karakter Melalui Penguatan Nilai Huyula di SMK Negeri 1 Limboto: Penelitian - Rasid Yunus; Zulfikar Adjie; Sanri J. Dotutinggi; Nurlaila Dawanggi (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The strengthening of character education through local cultural values has become an essential requirement in shaping competent and morally grounded students. This community service initiative aims to promote the implementation of the Huyula values which encompass mutual cooperation , responsibility, and social awareness in the character development of students at SMK Negeri 1 Limboto in a participatory and sustainable manner. The methodology employed a participatory approach with stages including initial observation, needs analysis, program formulation, coordination with the school, implementation of interactive socialization, as well as evaluation and reflection. Socialization was conducted through presentations, discussions, situational simulations, educational games, and collective reflection, with active student participation in analyzing real-life daily experiences. Data collection instruments consisted of observation questionnaires using a Likert scale, distributed to 125 students, followed by evaluation of 40 students in a representative sample. The results demonstrated a significant improvement in the implementation of Huyula values, evidenced by students’ awareness of linking academic achievement with character, their ability to interact across diverse backgrounds, understanding gained through daily experiences, and active participation in collective activities. The systematic and sustainable strengthening methods proved effective in fostering students’ intrinsic motivation to practice Huyula values in school life. This initiative underscores that character education based on local culture not only reinforces theoretical understanding but also cultivates tangible behaviors reflecting togetherness, responsibility, and social care, making it a relevant model for application in other vocational schools.